Pemberdayaan Masyarakat Melalui Pengelolaan Sampah (Studi Kasus di Bank Sampah Pelita Harapan, Kelurahan Ballaparang, Kecamatan Rappocini, Makassar) - Saleh, Muhammad (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Community empowerment is one element that enables a community can develop themselves and achieve progress. This study aims to describe the process of community empowerment and benefits in the waste management system through the principle of 3R waste banks that are in the Trash Bank Pelita Harapan village Ballaparang RW 04. Type of research is descriptive qualitative. Data collected by observation, interviews (interview), and documentation. Testing and analysis of data is done by triangulation of data and classifying data is systematically then outlines the existing data in the field that describes the form of community empowerment in the process of waste management. The results showed that community empowerment is used as a method in conducting waste management through waste bank system has increased in terms of the quality of the environment is clean and appears to be more community participation has increased . It was concluded that the descriptive stage to empower people is not easy and fast but requires a systematic process that starts from the stage of socialization, planning, implementation, and evaluation tools are required to analyze the success of community empowerment through the bank system trash. Keywords : Community Empowerment, Waste Management, Waste Bank, 3R<br style="text-transform: none; line-height: normal; text-indent: 0px; letter-spacing: normal; font-style: normal; font-variant: normal; font-weight: normal; word-spacing: 0px; white-space: normal; orphans: 2; widows: 2; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />